Hubungan antara Kadar Vitamin D dengan Kejadian Kanker Kolorektal: Studi Kasus dengan Pendekatan Berbasis Bukti - Kairupan, Timothy S.; Sukarno, Inka A. T.; Wulandari, Yohannessa; Manikam, Nurul R. M. (e-CliniC, 2026)
Abstract: Colorectal cancer is the third most common malignancy worldwide and the second leading cause of cancer-related death in developing countries. Vitamin D is known to play a role in inhibiting the progression of cancer cells. Vitamin D deficiency is prevalent in both developed and developing countries. Several studies have suggested an association between vitamin D levels and the incidence of colorectal cancer. This study aimed to determine the association between vitamin D levels and the incidence of colorectal cancer. A comprehensive literature search was conducted across PubMed, Cochrane Library, EBSCOhost, and ProQuest databases. Article selection followed predefined eligibility criteria through title and abstract screening, full-text review, and assessment of inclusion and exclusion criteria. Critical assessment tools and levels of evidence of the final articles are based on the Oxford Center for Evidence-Based Medicine. Four studies met the inclusion criteria, consisting of one meta-analysis and three cohort studies. The results showed that all studies reported an association between vitamin D levels and colorectal cancer. All studies indicated that vitamin D deficiency is associated with an increased risk of colorectal cancer. In conclusion, there is an association between vitamin D deficiency and the incidence of colorectal cancer. Keywords: adults; vitamin D; colorectal cancer   Abstrak: Kanker kolorektal merupakan kanker ketiga terbanyak didunia dan penyebab kematian kedua terbanyak yang menyebabkan kematian di negara berkembang. Vitamin D memiliki peran dalam menghambat perkembangan dari sel kanker. Defisiensi vitamin D cukup tinggi di negara maju dan berkembang. Beberapa penelitian menunjukkan hubungan vitamin D dengan kejadian kanker kolorektal. Penelitian ini bertujuan untuk mengetahui hubungan antara kadar vitamin D dengan kejadian kanker kolorektal. Pencarian literatur dilakukan pada Pubmed, Cochrane Library, EBSCOhost, dan ProQuest dengan kriteria eligibiltas yang ditentukan oleh penulis. Penyeleksi artikel dilakukan dengan penapisan judul atau abstrak, telaah teks lengkap, dan menentukan terpenuhinya kriteria inklusi dan eksklusi. Critical assessment tools and levels of evidence dari artikel terpilih mengacu pada Oxford Centre for Evidence-Based Medicine. Pencarian literatur mendapatkan empat studi yang memenuhi kriteria, yaitu satu studi meta-analisis dan tiga studi kohort. Keempatnya menunjukkan adanya hubungan kadar vitamin D dan kanker kolorektal. Hasil telaah keempat studi menunjukkan bahwa kadar vitamin D yang rendah dapat meningkatkan kejadian kanker kolorektal. Simpulan penelitian ini ialah terdapat hubungan antara kadar vitamin D dengan kejadian kanker kolorektal. Kata kunci: dewasa; vitamin D; kanker kolorektal